Human Resources Churning - Pirrolas, Olga Alexandra Chinita; Correia, Pedro Miguel Alves Ribeiro (Encyclopedia (Basel, Switzerland), 2023)
The term churning is defined by a multifaceted approach and is quite a complex concept that has been gaining relevance in the field of human resources, due to the problematic loss of investment, originating from the voluntary exits of worker-associated costs. This phenomenon is a direct result of the rising competitive job market, causing employees to leave organizations and carry with them all the knowledge and experience acquired in the starting organization, an organization which invested in the development of its workers. Even though churning is aligned with human resource practices, it is considered a multifaceted concept because of the different contexts in which it interferes, such as economic context, per activity sector, clients, the type of organization, geographic location, etc. Although, despite its own complexity, churning is related to turnover; however, there are differences between these two concepts. While turnover is linked to the workers’ rotation within an organization, churning is mainly focused on the costs associated with voluntary exits from workers. It is simply linked to investment losses inside an organization, which has the main goal of creating mechanisms that allow the creation of awareness in organizations about the relevancy of action using strategic measurements of holding in order to minimize the churning rate, and in this way, reducing the unexpected costs, creating revenue, increasing proficiency, standing out in business activity, bettering nimbleness and expanding profits. This initial manuscript introduces the churning concept in human resources, the main causes of churning, as well as approaching how organizations take action in order to appease this event using literature, which lacks major advertising and given relevance to its pertinence in human resources. Through the analysis of the existing, this entry was guided with the objective of demystifying the subject of human resource churning.